Abolition of Tax on Acquisition of Immovable Property: A Tool to Suppress the Negative Consequences of Covid-19 or a Politicum? - Radvan, Michal; Papavasilevská, Sandra (Public Governance, Administration and Finances Law Review, 2021)
The tax on acquisition of immovable property was abolished on September 26, 2020 in the Czech Republic. One of the reasons mentioned in the explanatory report to the Act was the statement that the abolition deals with the effects of this virus on society. The main aim of the article is to answer the question of whether the abolition of the tax on acquisition of immovable property is a tool to suppress the negative consequences of Covid-19 or a politicum. To get the answer, it is necessary to shortly describe the tax on acquisition of immovable property and its structural components and make a basic comparison with the other EU Member States. We also summarise the pros and cons of the tax and related findings of the Constitutional Court. As the property transfer tax is connected with the income tax and there were several amendments in the proposal, it is needed to analyse these changes. Based on the research, it is possible to conclude that the abolition of the tax on acquisition of immovable property is definitely not a tool to suppress the negative consequences of Covid-19; it is just a politicum: political parties believe that the abolition of the transfer tax brings them more voices in the elections.